HUBUNGAN KUALITAS PELAYANAN PETUGAS PENDAFTARAN DENGAN KEPUASAN PASIEN BPJS RAWAT JALAN DI PUSKESMAS AIKMEL TAHUN 2022 - Anisa Ratna Dewi; M. Adnan (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
The ability of officers to meet patient needs can be measured by the level of patient satisfaction. There are patients who complain and complain to the registration officer, the complaint shown to the clerk at the registration is in the form of a complaint about the length of time in providing service, so that the patient waits long and the officers are less friendly in providing services. This study aims to determine the relationship between the service quality of registration officers and the satisfaction of outpatient BPJS patients at the Aikmel Health Center. This study is an analytic observational study with a cross sectional data design, the sample in this study was 85 respondents who were outpatient BPJS patients at Aikmel Health Center. The collection tools and methods used are questionnaires through the interview method conducted from April to July 2022. The data analysis used is univariate and bivariate analysis with Kendall's test. The results of the Kendall's tau test showed that the service quality of the registration officer was significantly related to patient satisfaction. It was known that the percentage of patients who were satisfied was higher, namely 43 people with a percentage (50.6%) compared to patients who felt very satisfied, amounting to 37 people with a percentage (43). ,5 %) and those who feel dissatisfied are 7 people with a percentage (5,9 %). The results of the bivariate analysis with the Kendall's tau test were obtained that the p value (Approx.Sig) = 0.000 <0.05 which means (significant) so that the hypothesis is accepted. The results showed that patients were satisfied with the service quality of the registration officer at the Aikmel Health Center, the better the service quality.